(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
Infinity and continuity are two recurring themes in Danie Strauss’s philosophy of mathematics based on Herman Dooyeweerd’s Philosophy of the Cosmonomic Idea. Stressing the relevance of the distinction between law and subject, this paper provides some marginal comments on Strauss’s and Dooyeweerd’s views on mathematics, which may be influenced by intuitionism, constructivism and essentialism.